Impact of High‐Temperature Annealing on Boron Containing AlN Layers Grown by Metal Organic Vapor Phase Epitaxy. Issue 16 (21st July 2020) - Rettig, Oliver; Scholz, Ferdinand; Li, Yueliang; Biskupek, Johannes; Kaiser, Ute; Hagedorn, Sylvia; Weyers, Markus; Müller, Raphael; Thonke, Klaus
Abstract : Herein, the impact of high‐temperature (HT) annealing on the crystalline structure of metal organic vapor phase epitaxy (MOVPE)‐grown boron‐containing AlN layers is investigated. High‐resolution X‐ray diffraction studies reveal AlBN in the wurtzite configuration for nonannealed 300 nm‐thick layers containing several percent of boron. After 3 h of annealing at 1700 °C, the AlBN‐related reflex is weakened, showing a strong impact of the HT treatment on the crystalline structure of this material. After annealing, high‐resolution transmission electron microscopy micrographs reveal grain formation with moiré patterns, giving strong evidence of different crystal phases or orientations, alongside well‐oriented wurtzite regions. High‐angle annular dark‐field (HAADF) imaging and electron energy loss spectroscopy indicate stronger compositional inhomogeneities for the annealed sample in comparison with the as‐grown layer, most likely related to phase separation between AlN and BN. In addition, a significant diffusion of B out of the surface region is observed. AlBN with about ten times a lower boron content, for which defect propagation from the AlN template into the AlBN layer is visible, shows a much more homogeneous contrast in HAADF investigations after annealing, although the formation of granular structures is still observed. Abstract : Herein, the impact of high‐temperature annealing on the crystalline structure of MOVPE‐grown boron‐containing AlN layers is investigated. After annealing, grain formation with parasitic phases and stronger compositional inhomogeneities goes alongside well‐oriented wurtzite crystalline phases of the epitaxial layer. In addition, a significant diffusion of B out of the surface region is observed.